On a Class of Solvable Difference Equations - Stevo Stević; Mohammed A. Alghamdi; Naseer Shahzad; Dalal A. Maturi (Abstract and Applied Analysis)
A class of difference equations which can be solved in closed form is presented in this paper. Obtained formulas for the solutions are used in the study of the asymptotic behavior of their solutions in a particular case.